Developing future medical educators in an Australian medical program: supervisors' reflections on the first four years of MD Professional Project implementation. Issue 1 (1st January 2020) - McLean, Michelle; Tepper, Carmel; Maheshwari, Neelam; Brazil, Victoria; Moro, Christian
ABSTRACT: Background: Increasingly, professional bodies expect doctors to not only provide patient care but also educate students, trainees and patients. Few medical students, however, receive formal tuition in terms of the theory and practice of medical education. A curriculum restructure from an MBBS to a Doctor of Medicine (MD) program provided an opportunity to develop three Masters streams: Clinical research, Capstones and educational Professional Projects. This submission describes how one Australian medical school is preparing some students for their future roles as medical educators through MD Professional Projects. Design: Framed by the 12 roles of the medical 'teacher', most students undertaking these projects take on Resource Developer (including simulation) and Assessor roles. For those choosing resource development (excluding simulation) or assessment, the Association for Medical Education (AMEE) Student Essential Skills in Medical Education (ESME) Course is compulsory. For those choosing educational research, the ESME Course is optional. Outcomes: By December 2020, four MD cohorts will have graduated with 69 students having undertaken educational MD Professional Projects, with fifty-one completing the ESME Course. MD students have created a range of resources for the curriculum, their colleagues and the local healthcare community. In addition to the expected learning we identified additional value-added outcomes for learners (e.g. skill development), the curriculum (e.g. areas of difficulty), academic supervisors' roles (e.g. role-modelling) and for the health care community (e.g. as expert reviewers). Conclusions: Engaging in scholarly activities such the ESME Course and developing learning resources not only provided MD students with a more in-depth theoretical knowledge in a range of clinical areas, but also developed skills that would prepare them for their future roles as medical educators. As supervisors, we identified the value these projects add to the broader health community as well as personal and professional benefits for ourselves.